2013
DOI: 10.2478/v10222-012-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life Extension of Shrimp (White) Using Modified Atmosphere Packaging

Abstract: Wild caught shrimp can have a shortened shelf life compared to farm raised shrimp due to handling and on-ship limitations. The loss of freshness in shrimp is partly due to autolytic reactions caused by endogenous enzymes such as polyphenol oxidase. The objective of this study was to determine the effect of sulfi tes combined with modifi ed atmosphere packaging (MAP) on the shelf life of non-frozen shrimp. Fresh South Atlantic white shrimp were subjected to one of four treatments, no bisulfi te rinse-air packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Hx is produced by ATP degradation, which is as follows: ATP→ADP→AMP→IMP→HxR→Hx (Kalleda et al . ). Hx is an acceptable indicator to reflect freshness of aquatic products because it causes off‐flavors (Özogul et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hx is produced by ATP degradation, which is as follows: ATP→ADP→AMP→IMP→HxR→Hx (Kalleda et al . ). Hx is an acceptable indicator to reflect freshness of aquatic products because it causes off‐flavors (Özogul et al .…”
Section: Resultsmentioning
confidence: 97%
“…d), which is similar to the report of Kalleda et al . (). Besides, the rising rate of Hx for shrimp stored at 6C was higher than those stored at −3, 0 and 3C.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have been carried out on alternative methods of food preservation for the effective extension of shelf life in seafoods such as use of antimicrobials (Gelman, Glatman, Drabkin, & Harpaz, 2001), organic acids (Benner, Miget, Finne, & Acuff, 1994), modified atmosphere packaging (Kalleda et al, 2013), etc. There is an increasing consumer demand for high quality, minimally processed, additive-free sea foods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have tested 60:40 CO 2 :N 2 ratios and studies from our group with other meat types found lower CO 2 with N 2 and O 2 mixtures were successful in extending shelf life (Naas et al, 2013;Kalleda et al, 2013).Three salmon portions (10, 25 and 115 g) were placed in foam trays (C976 Sealed Air Cryovac, Duncan, SC) (8¾ * 6¾ * 15/8 ″). The nisin solution was spread on the surface of fillets using a sterile spreader to obtain a final nisin concentration of 400 IU/g.…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%